Spiro‐Driven Ferroelectric Coordination Polymer Exhibiting Distinct Phase Transitions Under Thermal and Pressure Stimuli - Du, Zi‐Yi; Xie, Miao; Qiu, Wenbo; Han, Ding‐Chong; Zhang, Shi‐Yong; Zeng, Ying; Cai, Weizhao; Nakamura, Takayoshi; Huang, Rui‐Kang; He, Chun‐Ting (Angewandte Chemie International Edition, 2025)
Controllable strategies for the design of molecular ferroelectrics have been actively pursued in recent years due to their promising applications in modern electronic devices. In this work, we present a spiro‐driven approach for the design of a new class of molecular ferroelectrics. Using 2‐morpholinoethanol (MEO) as a bidentate chelating ligand and the SCN⁻ anion as a bridging co‐ligand, we obtained a neutral chain‐like ferroelectric coordination polymer, [Cd(MEO)(SCN)₂]. Interestingly, it undergoes both a thermal‐induced phase transition, driven by ring‐conformational flipping of the spiro‐like [Cd(MEO)] fragment, and a pressure‐induced transition, triggered by significant deformation of the spring‐like [Cd(SCN)₂]∞ helical chain. Unlike most previously reported ferroelectric coordination polymers, which often rely on organic cationic guests, this work introduces a new avenue for designing neutral ferroelectric coordination polymers. Overall, the spiro‐driven strategy provides valuable insights and a novel structural motif for the development of advanced molecular ferroelectrics. Here we report the first example of a 1D spiro‐based ferroelectric coordination polymer, which exhibits distinct phase transitions under thermal or pressure stimuli, triggered by the flipping of a spiro ring fragment as well as the deformation of the main chain.